An Efficient Methodology for Encrypting Audio Data by Combining Rijndael and Steganography Algorithms - Mohammed, Sajaa G.; Al-Mothafar, Nuhad Salim (Iraqi Journal of Science, 2025)
Data security and its characteristics are considered one of the most important requirements of the modern era, as this generation is in rapid digital development. Therefore, it needs an effective methodology for a strong and effective encryption algorithm, by incorporating the standard encryption algorithm known as Rijndael. And steganography. The goal of this study is to transfer and store audio data with complete confidentiality and security. This study converts audio data into a 256  bit audio sample that we use for the purpose of encryption using the Rijndael algorithm, as this algorithm is known for its strength and for winning many awards. The principle of this algorithm’s work is to create multiple blocks of different block sizes and keys. We create keys for the purpose of encryption, and they are integrated into audio files using the developed data steganography technique. Saving the data is done using an image with the bmp extension. After that, we expose these images to compression to know and evaluate whether the steganography is successful. After that, we return it, remove the compression, and decrypt it. We note the return of the original text. The goal of this proposed methodology is to protect audio data from attacking persons and reduce the chances of revealing this data. This methodology is used for the purpose of transferring, storing, and safely preserving secret audio files with a security aspect. This research has one of its most important features in that it combines the strength of encryption, which is represented by the Rigndael algorithm, and the strength of data hiding technology, which resulted in the time of breaking the code and returning it in a record time of up to 99.9%. It also gives a developed and innovative methodology, for securing, transferring, storing and protecting audio data in all modern digital fields.